2015
DOI: 10.1002/cbf.3098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of novel curcumin‐encapsulated chitosan–bioglass drug on bone and skin repair after gamma radiation: experimental study on a Wistar rat model

Abstract: Radiation therapy contributes to a significant increase in bone osteoporosis and skin loss. Various natural health products might be beneficial to reduce bone and skin alterations. Curcumin (CUR) medicines derived from natural plants have played an important role in health care. This study aims at synthesizing and evaluating the performance therapy of CUR-encapsulated bioglass-chitosan (CUR-BG-CH). In vitro, the antioxidant assay was evaluated by using 1,1-diphenyl-2-picrylhydrazyl free-radical (DPPH) scavengi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Numerous studies on the effects of natural or synthetic antioxidants on collagen deposition and on antioxidant defense have generated highly conflicting data, depending on the experimental system used. However, with various wound healing models, it has been repeatedly demonstrated that complex plant extracts containing active secondary metabolites (polyphenols, flavonoids, and alkaloids) [42, 43] and components of collagen-inducing polysaccharides, such as chitosan, and antioxidants such as curcumin [45] and resveratrol [46] ameliorated wound healing and increased skin collagen deposition, while suppressing proinflammatory markers. ANT extract from black soybean seed coats has been shown to decrease inflammation by suppressing the translocation of NF- κ B p65 into the nucleus of human dermal fibroblasts and keratinocytes [11].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies on the effects of natural or synthetic antioxidants on collagen deposition and on antioxidant defense have generated highly conflicting data, depending on the experimental system used. However, with various wound healing models, it has been repeatedly demonstrated that complex plant extracts containing active secondary metabolites (polyphenols, flavonoids, and alkaloids) [42, 43] and components of collagen-inducing polysaccharides, such as chitosan, and antioxidants such as curcumin [45] and resveratrol [46] ameliorated wound healing and increased skin collagen deposition, while suppressing proinflammatory markers. ANT extract from black soybean seed coats has been shown to decrease inflammation by suppressing the translocation of NF- κ B p65 into the nucleus of human dermal fibroblasts and keratinocytes [11].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, with various wound healing models, it was repeatedly demonstrated that either complex plant extracts containing active secondary metabolites (triterpenes, polyphenols, alkaloids, etc.) [ 18 , 51 ] or a composition of collagen inducing polysaccharides like chitosan and antioxidants such as curcumin [ 52 ] or resveratrol [ 53 ] ameliorated wound healing increasing skin collagen deposition, while suppressing proinflammatory iNOS and myeloperoxidase, decreasing pathologically elevated levels of MDA and hydrogen peroxide, and improving enzymatic antioxidant defence. Recent studies showed that collagen peptides from fish skin remarkably promoted both wound healing and angiogenesis in different experimental settings [ 10 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cross-linked hydrogel films loaded with gentamicin sulfate displayed sustained drug release, in addition to effectively suppressing bacterial proliferation along with protecting the wound from infection [ 123 ]. Curcumin-encapsulated bioglass-chitosan, which is promising for wound healing applications, displayed higher 1,1-diphenyl-2-picrylhydrazyl and superoxide free radical quenching activities compared with unmodified curcumin, antibacterial activity against Staphylococcus aureus , and reduction in tumor necrosis factor- â production [ 124 ].…”
Section: Applicationsmentioning
confidence: 99%